2011
DOI: 10.1186/bcr3044
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density and breast cancer risk: the role of the fat surrounding the fibroglandular tissue

Abstract: IntroductionBoth the percent of mammographic density and absolute dense (fibroglandular) area are strong breast cancer risk factors. The role of non-dense (fat) breast tissue is not often investigated, but we hypothesize that this also influences risk. In this study we investigated the independent effects of dense and fat tissue, as well as their combined effect on postmenopausal breast cancer risk.MethodsWe performed a nested case-control study within the EPIC-NL cohort (358 postmenopausal breast cancer cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…In a recent meta-analysis, Pettersson et al [7] found a strong inverse association between absolute non-dense area and breast cancer risk, independent of dense area. This observation is supported by other studies [10,11], although not all [12,13].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In a recent meta-analysis, Pettersson et al [7] found a strong inverse association between absolute non-dense area and breast cancer risk, independent of dense area. This observation is supported by other studies [10,11], although not all [12,13].…”
Section: Introductionsupporting
confidence: 80%
“…Stone et al [12] also found an inverse association which was lost after adjustment for dense area. On the other hand, Lokate et al [13] found a positive association between non-dense area and breast cancer risk. These discrepant results have been thought to be due to the difference in the mammogram view used for the evaluation of non-dense area.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, estrogen and growth factors may influence not only the dense area, but the stroma and the surrounding adipose tissue. Importantly, others have observed that fibroglandular and fat tissue may have independent effects on breast cancer development [40].…”
Section: Discussionmentioning
confidence: 99%
“…Higher absolute nondense area (i.e., higher amounts of breast adipose tissue) has been linked with both increased [8] and decreased [9] breast cancer risk. In a recent meta-analysis including data from 13 case-control studies, absolute nondense area was inversely associated with breast cancer risk (odds ratio [OR] for a one standard deviation increment in absolute nondense area among postmenopausal women=0.85, 95 % CI 0.75-0.96) [10]; however, because of between-study heterogeneity, it remains unclear if the inverse association between the absolute nondense area and breast cancer risk is independent of the absolute dense area.…”
mentioning
confidence: 99%